Tinjauan Yuridis terhadap Penyelesaian Sengketa Tanah di Jakarta Barat - Istiqomah Istiqomah; Tarmudi Tarmudi; Nova Konny Umboh; Vincent Emmanuel Hartanu (Jurnal Syntax Admiration, 2024)
T Land dispute resolution is a complex issue in Indonesia, especially in urban areas such as West Jakarta. These disputes often involve the sale and purchase of the land in question, as in case Number 59/Pdt.G/2023/PN Jkt.Brt. This study aims to analyze juridically the settlement of land disputes and how they are implemented in the Indonesian legal system. The method used in this study is normative legal research that focuses on literature review. The results of the study show that the implementation of mediation as one of the dispute resolution methods provides equal justice for both parties, and can result in a peace agreement that has legal force. The conclusion of this study is that the mediation mechanism has great potential in resolving land disputes more effectively than the litigation route.